To simplify the expression 12r^2t^8/8rt^5, we can apply the commutative and associative properties of real numbers and the properties of exponents.
First, let's use the commutative property to rearrange the terms in the numerator:
12r^2t^8 = 12t^8r^2
Next, we can use the associative property to group the terms in the numerator:
12t^8r^2 = (12t^8)(r^2)
Now, let's simplify the expression within the parentheses:
12t^8r^2 = (12)(t^8)(r^2)
Finally, let's use the properties of exponents to simplify the expression further:
(12)(t^8)(r^2) = 12t^(8-1)r^(2-1) = 12t^7r
Therefore, the simplified expression is 12t^7r.
Use the commutative and associative properties of real numbers and the properties of exponents to simplify the expression.
12r^2t^8/8rt^5
5 answers
-30y0
The expression -30y^0 can be simplified as follows:
The property of any number raised to the power of 0 is equal to 1. Therefore, y^0 = 1.
Substituting this value into the expression, we have:
-30y^0 = -30(1) = -30
So, the simplified expression is -30.
The property of any number raised to the power of 0 is equal to 1. Therefore, y^0 = 1.
Substituting this value into the expression, we have:
-30y^0 = -30(1) = -30
So, the simplified expression is -30.
Evaluate the expression.
-3^2
-3^2
To evaluate the expression -3^2, we need to follow the order of operations, which states that we should perform any exponentiation before any multiplication or negation.
First, we must square the number 3.
3^2 = 3 * 3 = 9
Then, we apply the negative sign to the result:
-3^2 = -9
Therefore, the value of the expression -3^2 is -9.
First, we must square the number 3.
3^2 = 3 * 3 = 9
Then, we apply the negative sign to the result:
-3^2 = -9
Therefore, the value of the expression -3^2 is -9.